Valuing Urban Agriculture in Indonesia: Cultural Ecosystem Services and Willingness to Pay in Rapidly Urbanizing Cities - Puspitasari, Ratih Hesty Utami (Indonesian Scientific Publication, 2025)
Urban agriculture (UA) is increasingly recognized as a vital strategy for enhancing urban resilience, social equity, and ecological sustainability, particularly in rapidly urbanizing regions such as Indonesia. This study aims to evaluate the willingness to pay (WTP) for urban ecosystem services, with a particular focus on cultural and provisioning services delivered by UA in Indonesian cities. Using the Contingent Valuation Method (CVM), a structured survey was administered to assess public preferences and economic valuation of UA benefits. Logistic regression analysis was employed to identify the socio economic predictors of WTP. In addition, qualitative literature and comparative case studies were integrated to contextualize valuation findings within broader socio political and environmental frameworks. The results reveal strong public support for UA, with higher WTP values associated with cultural ecosystem services, particularly those linked to heritage, aesthetics, and community identity. Key predictors of WTP include income, education, environmental concern, and prior exposure to UA. Furthermore, regional differences highlight the role of cultural and policy contexts in shaping valuation outcomes. Discussion emphasizes the methodological limitations of CVM in capturing intangible values and advocates for mixed methods approaches that incorporate ethnographic and participatory tools. International case studies from cities such as Medellín, Bangkok, and Shanghai provide policy insights for effective UA integration, highlighting the importance of inclusive planning, cross sector collaboration, and legal recognition of UA practices. In conclusion, UA offers a multidimensional solution to urban challenges in Indonesia, providing environmental, cultural, and social co benefits. The study recommends embedding UA into participatory urban planning and leveraging valuation data to support equitable policy design.